2021
DOI: 10.3390/molecules26175402
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Antibacterial and Antifungal Activity of Biogenic Silver and Copper Nanoparticles: The First Report of Applying Biogenic Nanoparticles against Pilidium concavum and Pestalotia sp. Fungi

Abstract: There is increased attention paid to metallic nanoparticles due to their intensive use in various branches of agriculture and biotechnology, such as pest management, nanosensors, gene delivery, seed treatment, etc. There has been growing interest in applying environmentally friendly strategies for synthesizing nanoparticles without using substances which are hazardous to the environment. Biological practices for the synthesis of nanoparticles have been considered as possible ecofriendly alternatives to chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Furthermore, other authors have reported that fungal hyphae showed the formation of pits and pores against different pathogenic isolates of the same A. solani fungus after being treated with silver nanoparticles [ 20 ]. In addition, Bayat et al [ 40 ] reported that AgNP could successfully inhibit spore germination in B. cinerea in a concentration-dependent manner. AgNP application on Phytophthora parasitica and P. capsici caused a significat inhibition of the on-zoospore germination and germ tube elongation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other authors have reported that fungal hyphae showed the formation of pits and pores against different pathogenic isolates of the same A. solani fungus after being treated with silver nanoparticles [ 20 ]. In addition, Bayat et al [ 40 ] reported that AgNP could successfully inhibit spore germination in B. cinerea in a concentration-dependent manner. AgNP application on Phytophthora parasitica and P. capsici caused a significat inhibition of the on-zoospore germination and germ tube elongation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…16 In vitro experiments were performed to evaluate the antimicrobial susceptibility of microorganisms and the antimicrobial activity of biosynthesized NPs on Pseudomonas aeruginosa bacteria. 98 The results showed that CeVO 4 NPs have excellent antibacterial activity against Streptococcus mutans and Streptococcus pyogenes with MIC values at 200 mg mL À1 and against Vibrio cholera, Salmonella typhi, and Shigella flexneri with MIC values at 350 mg mL À1 . 16 Microsporum canis, Trichophyton rubrum, Trichophyton mentagrophytes, and Aspergillus niger were all eliminated by CeVO 4 NPs, and the NPs showed antifungal action against Candida albicans, Aspergillus niger and Aspergillus clavatus.…”
Section: Antimicrobial Activity Of Cevo 4 Npsmentioning
confidence: 96%
“…ZnO NPs at concentrations above 3 mmol L −1 (244.2 mg L −1 ) significantly inhibit growth of pathogenic postharvest fungi Botrytis cinerea and Penicillium expansum [23,24]. AgNPs tested at concentration 1-100 ppm were found to be the more effective antimicrobial agent against fungal pathogens Botrytis cinerea and Pilidium concavum in comparison to CuNPs tested at same concentrations [25]. Botrytis cinerea growth inhibition was not demonstrated in an in vitro well test with CuO NPs at concentrations 5, 50, 100, and 200 mg L −1 [26].…”
Section: Introductionmentioning
confidence: 99%